2015
DOI: 10.3389/fevo.2015.00045
|View full text |Cite
|
Sign up to set email alerts
|

Niche separation of pollen beetle parasitoids

Abstract: Species with similar resource requirements are commonly assumed to competitively exclude each other, unless they differentiate their ecological niches. Hence, parasitoid wasps that use the same host species need to find some way to avoid competition. The aim of this study was to identify the role of volatile cues from oilseed rape plants and the larval host in niche separation between three coexisting parasitoid species. We examined how Phradis interstitialis, Phradis morionellus and Tersilochus heterocerus, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Additionally, several species of specialist parasitic wasp attack the larvae of pollen beetles, including Phradis interstitialis (Thomson), Phradis morionellus (Holmgren) and Tersilochus heterocerus (Thomson) which can have a significant impact on pollen beetle control (reviewed by Ulber et al (2010) and Williams and Cook (2010)). There is evidence that semiochemicals mediate prey location (Williams et al 2007b;Berger et al 2015). Exploiting the current knowledge of the semiochemistry of host location by parasitoids could enhance biocontrol of pollen beetles within an IPM system as this has been already been achieved for aphid species in arable cropping systems (Du et al 1998;Powell and Pickett 2003).…”
Section: Predation By Natural Enemiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, several species of specialist parasitic wasp attack the larvae of pollen beetles, including Phradis interstitialis (Thomson), Phradis morionellus (Holmgren) and Tersilochus heterocerus (Thomson) which can have a significant impact on pollen beetle control (reviewed by Ulber et al (2010) and Williams and Cook (2010)). There is evidence that semiochemicals mediate prey location (Williams et al 2007b;Berger et al 2015). Exploiting the current knowledge of the semiochemistry of host location by parasitoids could enhance biocontrol of pollen beetles within an IPM system as this has been already been achieved for aphid species in arable cropping systems (Du et al 1998;Powell and Pickett 2003).…”
Section: Predation By Natural Enemiesmentioning
confidence: 99%
“…Olfactometer studies found that the three main species of pollen beetle parasitoid were all attracted to volatiles from OSR in the bud stage; however, there was an interesting finding of niche separation between the three competing species as they each displayed preferences for volatiles from insect infestations at different stages of OSR development that corresponded to their preferred host growth stage (Jonsson et al 2005;Berger et al 2015). After landing on the host-plant, T. heterocerus female parasitoids have also been shown to be attracted to volatiles from their pollen beetle host larvae (Straka et al 2013;Berger et al 2015).…”
Section: Predation By Natural Enemiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the incidence of P. morionellus in OSR fields was supported by forest proximity, while the opposite was found for its sibling species P. interstitialis . This may add an additional dimension to the niche separation between these two Phradis species (Berger et al 2015 ). Both are parasitoids of the rape pollen beetle.…”
Section: Discussionmentioning
confidence: 99%